VERMIKOMPOS DARI BAHAN LIMBAH ORGANIK SAYURAN (STUDI KASUS: PASAR JATI, BANYUMANIK, SEMARANG) - Christian Dhana Indrajati (Jurnal Teknik Lingkungan, 2012)
Pasar Jati Banyumanik is a market which located in the middle of Perumnas Banyumanik area. The development of Banyumanik area increased resident and so the  level of consumption from year to year. With the increasing level of public consumption then the amount of organic solid waste in Pasar Jati Banyumanik increased too. The vegetable solid waste growing need more attention  so it can be utilized. As an alternative organic solid waste is using worm or vermicompost technology. The purpose of this study is to determine the content of macro nutrient from the vermicompost with vegetables used as worm food.